Constructivism and the phenomenology of moral deliberation - Ponzo, Alexander, author; Tropman, Elizabeth, advisor; Gorin, Moti, committee member; Cleary, Anne, committee member (Colorado State University. Libraries, 2017)
In this thesis I claim that constructivism is an attractive positon when it comes to explaining the nature of moral facts. The central tenet of constructivism is that moral facts are a function of what actual (or hypothetical) people think. According to constructivism, if it is true (for example) that murder is morally wrong, it is because some actual (or hypothetical) person or group of people under certain conditions thinks that murder is morally wrong. A primary competitor to constructivism is realism. Realism denies the central tenet of constructivism and instead holds that moral facts are objective; this means that the truth of moral facts does not depend on any person's or group of persons' attitudes regarding the object of moral evaluation. For realists, then, if murder is morally wrong it is not because any (actual or hypothetical) person or group of people thinks that it is wrong; for realists, this fact obtains regardless of what anyone thinks about it. I argue in Chapter One that there is a significant epistemological problem with the claim that moral facts are objective; namely, that it is hard to see how we could have moral knowledge if the truth of moral facts is not a function of what we think. I argue in Chapter Two that constructivism does not share the epistemological problem that realism has. This problem is significant and it should be enough, I submit, to push us into accepting constructivism over realism. While I devote the first chapter (and some of the second) to explaining what constructivism is and how it compares to other competing theories, this is not the only task of this thesis. My other central task is to examine two specific versions of constructivism—namely, the respective theories of Christine Korsgaard and Sharon Street—and find out whether each theory can maintain a plausible phenomenology of moral deliberation. In other words, I am interested in finding out whether each version of constructivism can give a plausible account of what it is like for people to engage in moral deliberation. Since it's possible to study the phenomenology of moral deliberation empirically (or by plausible speculation), we can compare how moral deliberation is actually experienced—or at least how it seems to be experienced—with how it would likely be experienced if the theories in question were true. Ultimately, I argue that the phenomenology of moral deliberation occasioned by Korsgaard's position is more plausible than the one occasioned by Street's because Korsgaard's position does a better job of preserving what we tend to think the experience of moral deliberation is like. A summation of this thesis can be given in the following way: I make a presumptive case for constructivism and, specifically, I argue that Korsgaard's constructivism is more attractive than Street's because, among other things, the phenomenology of moral deliberation occasioned by Korsgaard's position is more plausible than the one occasioned by Street's.
Keywords: moral deliberation; constructivism; phenomenology